Advances in Forest Ecophysiology: Stress Response and Ecophysiological Indicators of Tree Vitality - Nenad Potočić (Plants, 2023)
Back in the beginning of the year 2021, when the work on this Special Issue started, it was quite clear that the topics of tree stress response and the ecophysiological indicators of tree vitality were both current and important, but the attitude of the scientific community towards the idea of a Special Issue on the subject was yet to be determined [...]